Observation-based estimates of the mass absorption cross-section of black and brown carbon and their contribution to aerosol light absorption in East Asia. (1st September 2019) - Cho, Chaeyoon; Kim, Sang-Woo; Lee, Meehye; Lim, Saehee; Fang, Wenzheng; Gustafsson, Örjan; Andersson, August; Park, Rokjin J.; Sheridan, Patrick J.
Abstract: In this study, we estimated the contribution of black carbon (BC) and brown carbon (BrC) to aerosol light absorption from surface in-situ and aerosol robotic network (AERONET) columnar observations. The mass absorption cross-section (MAC) of BC ( MAC BC ) was estimated to be 6.4 ± 1.5 m 2  g −1 at 565 nm from in-situ aerosol measurements at Gosan Climate Observatory (GCO), Korea, in January 2014, which was lower than those observed in polluted urban areas. A BrC MAC of 0.62 ± 0.06 m 2  g −1 (565 nm) in our estimate is approximately ten times lower than MAC BC at 565 nm. The contribution of BC and BrC to the carbonaceous aerosol absorption coefficient at 565 nm from the in-situ measurements was estimated at 88.1 ± 7.4% and 11.9 ± 7.4%, respectively at GCO. Similarly, the contribution of BC and BrC to the absorption aerosol optical depth (AAOD) for carbonaceous aerosol (CA), constrained by AERONET observations at 14 sites over East Asia by using different spectral dependences of the absorption (i.e., absorption Ångström exponent) of BC and BrC, was 84.9 ± 2.8% and 15.1 ± 2.8% at 565 nm, respectively. The contribution of BC to CA AAOD was greater in urban sites than in the background areas, whereas the contribution of BrC to CA AAOD was higher in background sites. The overall contribution of BC to CA AAOD decreased by 73%–87% at 365 nm, and increased to 93%–97% at 860 nm. The contribution of BrC to CA AAOD decreased significantly with increasing wavelength from approximately 17% at 365 nm to 4% at 860 nm. Highlights: We estimated the contribution of black carbon (BC) and brown carbon (BrC) to aerosol light absorption. We used surface in-situ and column AERONET data from Gosan in January 2014. The contribution of BC and BrC at 565 nm was estimated at 88.1±7.4% and 11.9±7.4%. The contribution of BC and BrC to AAOD was 84.9±2.8% and 15.1±2.8%, respectively. The contribution of BC to CA AAOD was greater in urban sites than in the background areas, whereas the contribution of BrC to CA AAOD was higher in background sites.